2005
DOI: 10.1126/science.1115616
|View full text |Cite
|
Sign up to set email alerts
|

Wanted: Women in Clinical Trials

Abstract: M ost biomedical and clinical research has been based on the assumption that the male can serve as representative of the species. This has been true in spite of increasing awareness of significant biological and physiological differences between the sexes, beyond the reproductive ones. Women and men differ in their susceptibility to and risk for many medical conditions, and they respond differently to drugs and other interventions. The close of the previous decade saw 8 out of 10 prescription drugs withdrawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 0 publications
1
46
0
7
Order By: Relevance
“…Despite calls for equality in recruitment and enrollment of clinical trials [34], women have continued to be underrepresented in many areas of research [17,20,28,30,44,50,53,59]. This may be due to the exclusion of pregnant women from many clinical trials for safety reasons but can also be due to differences in recruiting strategies resulting in few women being enrolled [59].…”
Section: Why Are Sex and Gender Important In Research?mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite calls for equality in recruitment and enrollment of clinical trials [34], women have continued to be underrepresented in many areas of research [17,20,28,30,44,50,53,59]. This may be due to the exclusion of pregnant women from many clinical trials for safety reasons but can also be due to differences in recruiting strategies resulting in few women being enrolled [59].…”
Section: Why Are Sex and Gender Important In Research?mentioning
confidence: 99%
“…This lack of gender representation and subgroup analysis has led to serious consequences. In 2005, 80% of drugs withdrawn from the US market were due to side effects and other issues impacting women that had not been studied during initial drug trials [50].…”
Section: Why Are Sex and Gender Important In Research?mentioning
confidence: 99%
“…Despite being a majority of the population, women's representation in scientific research on women still lags behind that of men's [42••, 51,52]. The reasons for this are varied: inequality in recruitment, women excluded because of pregnancy, and willingness to participate.…”
Section: Future Directionsmentioning
confidence: 99%
“…20 Despite this legislation, several reports have shown that in some cases, especially in the case of racial/ethnic minorities, women still may be underrepresented in biomedical research. 10,21,22 We examined beliefs and attitudes regarding vulnerability of women when they participate in biomedical research studies. Specifically, we examined whether people believed the benefits of including women of childbearing age outweigh the potential risks involved in their participation in these studies and if beliefs varied by sex or by race/ethnicity in a geographically and sociodemographically diverse group of adults.…”
Section: Discussionmentioning
confidence: 99%